Female Asthmatic Patients Have Higher Risk to Develop Gemifloxacin-Associated Skin Rash, Highlighting Unique Delayed Onset Characteristics - Chiou-Mei Wu; Po-Ju Wei; Yu-Ting Shen; Hsu-Liang Chang; Ying-Ming Tsai; Hung-Fang Pan; Yong-Chieh Chang; Yu-Ching Wei; Chih-Jen Yang (MDPI AG, 2019)
Gemifloxacin is a common oral antibiotic for lower respiratory tract infection worldwide. We noticed an uncommon delayed onset skin rash in patients who received Gemifloxacin. Therefore, we retrospectively reviewed all patients who received Gemifloxacin from 1 January 2011 to 31 May 2016 in a university-affiliated hospital in Taiwan. A total of 1358 patients were enrolled, of whom 36 (2.65%) had skin eruptions. The female patients had a significantly higher odds ratio (OR) 2.24 (95% confidence interval (CI) 1.11−4.53, p = 0.021) of having skin eruptions. A history of asthma was also a significant risk factor (OR 2.04, 95% CI = 1.01−4.14, p = 0.043). Female asthmatic patients had the highest risk of skin eruptions (10/129, 7.2%) with an adjusted OR up to 4.45 (95% CI = 1.81−10.93, p < 0.001) compared to male and non-asthmatic patients. Of note, up to 58.3% (21/36) of the patients experienced a skin rash after they had completed and stopped Gemifloxacin. The median onset time was on the second day (ranging one to five days) after completing treatment. We reported that female asthmatic patients have the highest risk of Gemifloxacin-associated skin eruptions in Asia and that they highlighted a unique delayed onset skin rash.